2008
DOI: 10.1111/j.1468-1293.2008.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of nevirapine during pregnancy: impact of pregnancy on pharmacokinetics

Abstract: ObjectivesTo determine the impact of pregnancy on the pharmacokinetics (PK) of nevirapine (NVP) during chronic dosing in HIV-infected women and appropriate NVP dosing in this population. MethodsTwenty-six pregnant women participating in two open-label Pediatric AIDS Clinical Trials Group studies (P1022 and P1026S) were evaluated. Each patient received 200 mg NVP every 12 h and had PK evaluations during the second or third trimester; these evaluations were repeated postpartum. Paired maternal and cord blood NVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
4
24
1
Order By: Relevance
“…The magnitude of change in sertraline concentrations varied from 29% decrease to 90% decrease (Freeman et al, 2008). In contrast to these observations, the oral clearance of nevirapine was not different during the third trimester of pregnancy and postpartum when evaluated in a population of unknown CYP2B6 genotypes (Capparelli et al, 2008). Because all of these drugs are eliminated by multiple cytochrome P450 enzymes, the effect of pregnancy on CYP2B6 activity cannot be conclusively evaluated from these studies.…”
Section: Introductioncontrasting
confidence: 45%
“…The magnitude of change in sertraline concentrations varied from 29% decrease to 90% decrease (Freeman et al, 2008). In contrast to these observations, the oral clearance of nevirapine was not different during the third trimester of pregnancy and postpartum when evaluated in a population of unknown CYP2B6 genotypes (Capparelli et al, 2008). Because all of these drugs are eliminated by multiple cytochrome P450 enzymes, the effect of pregnancy on CYP2B6 activity cannot be conclusively evaluated from these studies.…”
Section: Introductioncontrasting
confidence: 45%
“…An alternative approach is to dose NVP based on weight bands, which requires no calculations and is easy to implement in the developing world. The WHO selected weight bands rather than age for dosing in resource-poor countries, as obtaining an accurate age can be difficult due to poor record-keeping.NVP has been studied extensively in adults, and multiple population pharmacokinetics (PK) studies have been published (1,4,6,8,11,13,21,27). While many studies have looked at NVP in HIV-infected infants, children, and adolescents (12,15,17,23,26), no comprehensive population analyses have been performed to assess NVP across the pediatric age continuum.…”
mentioning
confidence: 99%
“…In collusion with other studies [1,18,19], we have observed that NVP-treatment causes more often the increase of ␥-GT than ALT and AST: after two years, ␥-GT levels reached a plateau in patients without hepatitis. This trend has been pointed out also by the Murphy et al meta-analysis [19].…”
Section: Discussionmentioning
confidence: 51%